2017
DOI: 10.1371/journal.pone.0179630
|View full text |Cite
|
Sign up to set email alerts
|

What do computer scientists tweet? Analyzing the link-sharing practice on Twitter

Abstract: Twitter communication has permeated every sphere of society. To highlight and share small pieces of information with possibly vast audiences or small circles of the interested has some value in almost any aspect of social life. But what is the value exactly for a scientific field? We perform a comprehensive study of computer scientists using Twitter and their tweeting behavior concerning the sharing of web links. Discerning the domains, hosts and individual web pages being tweeted and the differences between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…While we do not have a random sample of tweets to compare this to, studies of different user groups have shown high levels of information sharing among the group, e.g. computer scientists [49]. While those levels are higher than the levels in our data set, it is clear that URL information sharing is occurring and may reflect the incredible need for information in this uncertain time [4,5].…”
Section: Findings and Analysismentioning
confidence: 82%
“…While we do not have a random sample of tweets to compare this to, studies of different user groups have shown high levels of information sharing among the group, e.g. computer scientists [49]. While those levels are higher than the levels in our data set, it is clear that URL information sharing is occurring and may reflect the incredible need for information in this uncertain time [4,5].…”
Section: Findings and Analysismentioning
confidence: 82%
“…The research reported here has a twofold objective: to determine academics' motives for engaging in online social networking and the ways in which they use both generalist and academic networking sites. To this end, we address the gap in the literature on individual practices on SNS (Veletsianos and Kimmons, 2016;Schmitt and Jäschke, 2017). We also identify the main motives that deter some academics from using these platforms and, specifically, focus on those factors that dissuade them from using SNS professionally.…”
Section: Justificationmentioning
confidence: 99%
“…A majority of respondents to a survey conducted by Haustein et al (2014a) indicated that academic networking sites affected their professional lives both negatively (e.g., encouraging procrastination) and positively (e.g., aiding organization of research material). However, specialized academic networking sites are not the only tools scholars employ for scholarly identity endeavors; they also appropriate affordances of more general social media platforms such as Facebook and Twitter to promote themselves and their research (e.g., Priem and Costello, 2010; Schmitt and Jäschke, 2017). Activity surrounding recently published articles on academic networking sites such as Twitter may increase citations, predict citations and compliment citation metrics with measures of social impact (Priem and Costello, 2010; Eysenbach, 2011; Haustein et al , 2014b; Nabout et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ortega (2015a) found that humanists and social scientists frequently used Academia.edu and connected with other researchers, while biologists chose ResearchGate and did not make these connections as often. Computer scientists may choose platforms such as Twitter for both information-oriented and professional purposes (Schmitt and Jäschke, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%